Hallyu pop culture and the motivation of generation z in visiting South Korea - Irsan, Dimas Maulana; Khadijah, Ute Lies Siti Khadijah; Saefullah, Kurniawan; Novianti, Evi (Bricolage : Jurnal Magister Ilmu Komunikasi, 2024)
Popular culture is known to have an influence in building human behavioral intentions. Moreover, now, popular culture from South Korea or often referred to as "Hallyu" has become a phenomenon among Generation Z in Indonesia. Along with the "Hallyu" phenomenon that is occurring, data shows that there is an increase in the tourist trend to South Korea. This then raises the question of whether there is an influence of "Hallyu" on intentions to visit South Korea. Thus, this research aims to build a model and find out the influence of involvement in South Korean popular culture on the formation of intentions to visit South Korea. Data collection was carried out by distributing questionnaires online to 361 respondents from the population who like "Hallyu" popular culture in West Java. The data collected was then analyzed using Structural Equation Modeling (SEM). The findings of this research indicate that visiting intentions can be built by factors involving South Korean popular culture. Situational involvement has a significant influence on the formation of individual visiting intentions, but lasting involvement does not have a significant influence.